2013
DOI: 10.2147/ceg.s35163
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab treatment in Crohn's disease: an overview of long-term efficacy and safety in light of the EXTEND trial

Abstract: The advent of anti-tumor necrosis factor (TNF) therapies revolutionized the treatment of inflammatory bowel disease. Adalimumab is a subcutaneous anti-TNF agent indicated for use in patients with moderate-to-severe Crohn’s disease and those with moderate-to-severe ulcerative colitis. In both diseases, it can be used for both induction of remission and for maintenance of remission. This review focuses on its use in Crohn’s disease as described in the EXTEND (Extend the Safety and Efficacy of Adalimumab through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…A previous study showed similar findings with a 44.4% steroid-free rate during anti-TNF-α (IFX) treatment 19. Mucosal healing is the current goal of treating CD patients to reduce the need for hospitalizations and surgery 7. In our study, the mucosal healing rate was 25% after 6-12 months treatment, which is similar to the EXTEND trial of 27% at week 12 4.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study showed similar findings with a 44.4% steroid-free rate during anti-TNF-α (IFX) treatment 19. Mucosal healing is the current goal of treating CD patients to reduce the need for hospitalizations and surgery 7. In our study, the mucosal healing rate was 25% after 6-12 months treatment, which is similar to the EXTEND trial of 27% at week 12 4.…”
Section: Discussionsupporting
confidence: 88%
“…The safety and efficacy of ADA for CD have been extensively tested in Western countries, but much less so in Asian countries 3,6,7,8,9,10,11. In Japan, ADA was approved for CD treatment since 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 10 11 12 ] Adalimumab is a recombinant human IgG1 monoclonal antibody to TNFα that also affects receptor-bound TNFα. It is approved for use in children with enthesitis-related arthritis,[ 13 ] severe plaque psoriasis,[ 14 ] severe Crohn's disease,[ 15 ] and active JIA. [ 14 ] It has also been used in the patients with intraocular inflammation as a rescue therapy, and been shown to be effective in controlling uveitis in a pediatric group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the percentage of IBD patients taking biologics is lowest in India, where the coverage rate by public health insurance is low and IBD patients have to pay for most of their medical expenses. As biologics have been proven to improve the clinical and mucosal status of IBD patients, 7 determining whether the difference will affect the outcomes (such as operation rate, admission rate, or even mortality rate) needs a longer period of follow-up.…”
Section: Discussionmentioning
confidence: 99%